2022
DOI: 10.3389/fphar.2022.924429
|View full text |Cite
|
Sign up to set email alerts
|

Astragalus mongholicus Bunge (Fabaceae): Bioactive Compounds and Potential Therapeutic Mechanisms Against Alzheimer’s Disease

Abstract: Astragalus mongholicus Bunge (Fabaceae) (also known as Astragali radix-AR), a widely used herb by Traditional Chinese Medicine practitioners, possesses a wide range of pharmacological effects, and has been used to treat Alzheimer’s disease (AD) historically. Its bioactive compounds are categorized into four families: saponins, flavonoids, polysaccharides, and others. AR’s bioactive compounds are effective in managing AD through a variety of mechanisms, including inhibiting Aβ production, aggregation and tau hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 112 publications
(116 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, our sensitivity test showed that CHM users still had a lower risk of all-cause mortality than non-CHM users in patients with the CNS infections. Studies have shown that CHMs and associated natural compounds may be beneficial for neurological impairment in HIV/AIDS through anti-cognitive decline via the promotion of blood circulation and attenuation of oxidative stress, as well as anti-neuroinflammation and anti-HIV (Han et al, 2011;Cheng et al, 2015;Lin et al, 2015;Esposito et al, 2016;Zhao et al, 2016;Lee et al, 2017;Adebiyi et al, 2018;Long F. Y. et al, 2018;Zhang et al, 2018;Zeng et al, 2019;Qu et al, 2021;Dong et al, 2022;Xu et al, 2022;Xue et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our sensitivity test showed that CHM users still had a lower risk of all-cause mortality than non-CHM users in patients with the CNS infections. Studies have shown that CHMs and associated natural compounds may be beneficial for neurological impairment in HIV/AIDS through anti-cognitive decline via the promotion of blood circulation and attenuation of oxidative stress, as well as anti-neuroinflammation and anti-HIV (Han et al, 2011;Cheng et al, 2015;Lin et al, 2015;Esposito et al, 2016;Zhao et al, 2016;Lee et al, 2017;Adebiyi et al, 2018;Long F. Y. et al, 2018;Zhang et al, 2018;Zeng et al, 2019;Qu et al, 2021;Dong et al, 2022;Xu et al, 2022;Xue et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Chinese herbal medicine (CHM) has been used in patients with HIV/AIDS-related diseases (Tsai F. J. et al, 2017;Tsai et al, 2018;Sun et al, 2019;Ho et al, 2021;Jiang et al, 2022). CHMs and related natural compounds have been reported to have anti-cognitive, antineuroinflammatory, and anti-HIV activities (Han et al, 2011;Cheng et al, 2015;Esposito et al, 2016;Zhao et al, 2016;Lee et al, 2017;Adebiyi et al, 2018;Long F. Y. et al, 2018;Zhang et al, 2018;Zeng et al, 2019;Qu et al, 2021;Dong et al, 2022;Xu et al, 2022;Xue et al, 2022). These studies encourage the investigation of whether CHM could improve survival in patients with neurological diseases HIV/AIDS as a complementary therapy to conventional medicine.…”
Section: Introductionmentioning
confidence: 90%
“…International research on traditional Chinese medicine for the treatment of AD has focused on Chinese herbs [e.g., Morinda officinalis How , Astragali radix (Dong et al, 2022)] or active ingredients of Chinese herbs [e.g., polysaccharides , ginsenoside (Wu et al, 2022a), evodiamine (Pang et al, 2022), Huperzine A (Yan et al, 2022)], herbal prescriptions [e.g., Yi-Gan San (Yang et al, 2023), Yuan-Zhi Decoction (Wu et al, 2022b)], special therapies [e.g., Wuqinxi exercise (Luo et al, 2022), Tai Chi Quan (Wang et al, 2022)], and acupuncture (Cai et al, 2019;Yu et al, 2021a;Zheng et al, 2021;Hao et al, 2022) to improve memory and cognitive impairment in AD models, involving various mechanisms such as regulation of βamyloid and tau proteins, anti-oxidation, anti-neuroinflammation, modulation of autophagy and many other mechanisms. Among these, acupuncture is considered to be a highly promising alternative therapy for AD.…”
Section: Discussionmentioning
confidence: 99%
“…Herbal therapy is considered to be a very safe and approachable source of compounds for the treatment of NDDs ( Dong et al, 2022 ). Numerous plants in the literature specifically target PDE1 in the brain ( Helmi et al, 2020a ).…”
Section: Pde1 Inhibition and Natural Productsmentioning
confidence: 99%